Differentiated instruction, physical fitness, and motivation on PE learning outcomes: a literature review - Cori Apri Yeniarti; Padli Padli; Arsil Arsil; Ardo Okilanda (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
This systematic literature review examines how differentiated instruction, physical fitness, and learning motivation independently and interactively influence learning outcomes in physical education (PE). Drawing on peer-reviewed national and international studies published between 2018 and 2025, the review synthesizes evidence related to pedagogical practices, students’ physical readiness, and motivational processes in school-based PE. The findings indicate that differentiated instruction consistently enhances engagement and learning readiness, although its direct effects on psychomotor outcomes, particularly at the secondary level, remain limited. Physical fitness shows a stable association with motor performance and participation, while autonomous motivation supports sustained effort and persistence. However, most studies examine these factors in isolation, offering limited insight into their combined effects. This review highlights a clear gap in integrative research and underscores the need for comprehensive instructional models that align pedagogical, physiological, and motivational dimensions to improve PE learning outcomes.